1998
DOI: 10.1016/s0735-1097(98)00270-8
|View full text |Cite
|
Sign up to set email alerts
|

Production of oxidative products of nitric oxide in infarcted human heart

Abstract: The appearance of oxidative products of NO (NO2- and NO3-) in peripheral blood of patients with acute MI is the result of their increased release from infarcted heart during the inflammatory phase of myocardial ischemia. Further studies are needed to define the clinical value of these observations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 28 publications
2
24
0
2
Order By: Relevance
“…9 The understanding of the pathophysiology of cardiogenic shock complicating MI has recently evolved toward an appreciation of the role of systemic inflammation, including cytokine release and expression of inducible nitric oxide synthase (NOS). [10][11][12] Excessive NOS results in high levels of nitric oxide that, in turn, lead to inappropriate systemic vasodilatation, progressive systemic and coronary hypoperfusion, and myocardial depression. [10][11][12] Inhibition of NOS is a theoretically appealing approach to treatment of this high-risk population.…”
Section: The Triumph Randomized Controlled Trialmentioning
confidence: 99%
See 2 more Smart Citations
“…9 The understanding of the pathophysiology of cardiogenic shock complicating MI has recently evolved toward an appreciation of the role of systemic inflammation, including cytokine release and expression of inducible nitric oxide synthase (NOS). [10][11][12] Excessive NOS results in high levels of nitric oxide that, in turn, lead to inappropriate systemic vasodilatation, progressive systemic and coronary hypoperfusion, and myocardial depression. [10][11][12] Inhibition of NOS is a theoretically appealing approach to treatment of this high-risk population.…”
Section: The Triumph Randomized Controlled Trialmentioning
confidence: 99%
“…[10][11][12] Excessive NOS results in high levels of nitric oxide that, in turn, lead to inappropriate systemic vasodilatation, progressive systemic and coronary hypoperfusion, and myocardial depression. [10][11][12] Inhibition of NOS is a theoretically appealing approach to treatment of this high-risk population. Early singlecenter studies with isoform-nonselective NOS inhibitors were promising and suggested a substantial beneficial effect on survival.…”
Section: The Triumph Randomized Controlled Trialmentioning
confidence: 99%
See 1 more Smart Citation
“…NO originates from an L-arginine-dependent pathway [3]. In patients and animals with myocardial infarction, NO myocardial production increases its oxidation products (NO 2 and NO 3 : NOx) in coronary sinus blood [4,5]. Together with NO, there occurs an increase of prostacyclin (PGI 2 ) and thromboxane A 2 (TXA 2 ) in heart muscle as a result of activation of cyclooxygenase (COX) [6].…”
Section: Introductionmentioning
confidence: 99%
“…The interaction of ROS with membrane lipids and essential cellular biomolecule modification contribute to damage, leading to vasoconstriction and leukocyte adhesion on the endothelial surface (3,12,19). NO has been shown to be protective in I/R-induced damage by inhibiting platelet adhesion and aggregation and attenuating leukocyte adhesion (1,5,17,24). However, despite recent advances in therapeutics and the potential of antioxidant intervention, both the efficacy of ROS scavengers and the role of NO in the clinical setting remain undetermined (2,20,41).…”
mentioning
confidence: 99%